Screening Diatom Strains Belonging To Cyclotella Genus for Chitin Nanofiber Production Under Photobioreactor Conditions: Chitin Productivity and Characterization of Physicochemical Properties - Özkan, Altan; Özkan, Altan (Elsevier, 2023)
Diatom species belonging to Cyclotella and Thalassiosira genera have the unique and industrially relevant ability to biosynthesize and extrude pure chitin nanofibers. The current understanding of diatom-based chitin production is narrowed by the complete reliance on the performance of a single strain. This study aims to facilitate the development of a wider understanding for enhanced industrial utility. For this purpose, six Cyclotella strains were cultivated under standardized process conditions of a bubble column photobioreactor, and the resulting productions were characterized in terms of rate and physicochemical properties. A two-stage cultivation protocol was followed where the cells were cultivated under silicon replete and then following its complete consumption under silicon deplete conditions. All the strains produced chitin fibers of β-form with relatively constant average diameters, ranging from 48 to 58 nm. Chitin production rates and final concentrations as well as fiber number densities and length distributions were highly strain-dependent. Dissolved silicon availability controlled chitin biosynthesis: following its depletion, the productivity of all the strains increased drastically. Two strains of marine origin, C. cryptica CCMP 332 and C. cryptica CCMP 333, generated the most favorable outcomes for commercial-scale production and had final concentrations of 272 ± 9 mg/L and 316 ± 12 mg/L, and maximum production rates of 48 ± 2 mg/L-day and 51 ± 2 mg/L-day, respectively. The superior performance of these strains was due to (i) the extrusion of more fibers per fiber port, in the case of C. cryptica CCMP 333 as many as 20.7 ± 1.0. indicating free fiber accumulation in suspension, and (ii) the biosynthesis of longer fibers, mean fiber lengths varied from 15 to 20 μm during cultivation. This study demonstrates the importance of species selection and silicon availability for diatom-based chitin production in terms of rate, final concentration, and nanofiber fiber length distributions.
Keywords: Chitin; Diatom; Photobioreactor; Screening